Application of multi-functional chestnut shell in one-step preparing Fe3O4@C magnetic nanocomposite with high adsorption performance. Issue 8 (3rd August 2018) - Zhang, Lina; Han, Yuqi; Yang, Zhiwang; Su, Bitao
ABSTRACT: Chestnut shell (CS) acts as a multi-functional material in the one-step preparation of Fe3 O4 @C nanocomposite via hydrothermal method by using Fe(NO3 )3 as Fe source without adding any other additives. The characterized results show that under required hydrothermal conditions, a proper amount of CS can reduce a certain amount of adsorbed/enriched Fe 3+ to Fe 2+ to ensure the 2:1 molar ration of Fe 3+ to Fe 2+ and the in-situ formation of goal phase Fe3 O4 on the surface of the CS. Meanwhile, CS is carbonized to C material similar to graphene oxide. In the preparation process of the composite of Fe3 O4 @C, CS plays multiple roles, such as promoter, reductive agent, C-source, and template, to endow a certain morphology of the nanocomposite Fe3 O4 @C. The composite material shows good magnetic separability and adsorption property for methylene blue (MB) solution. Furthermore, the adsorptive kinetic behavior of the Fe3 O4 @C is investigated. The method is simple, fast, low cost and green and really realizes the full use of wasteful resource CS.